SITOTOKSISITAS XANTHORRHIZOL dari MINYAK ATSIRI RIMPANG Curcuma xanthorrhizaRoxb. terhadap SEL KANKER PAYUDARA YBM-1 - Zalinar Udin (Jurnal Kimia Terapan Indonesia, 2013)
Curcuma xanthorrhiza Roxb. (temulawak) known hascytotoxic activity against cancel cells. The active compoundofCurcuma xanthorrhizaRoxb., for several cancer cells isxanthorrhizole. This research would assay the cytotoxicactivity of volatile oil from Curcuma xanthorrhizaRoxb. 'srhizome toward YMB-1 breast cancer cell. The method wasdone by in-vitro with alamar blue dyed, and measuredtheabsorbance to observe the viability (%) of cell and IC,ovalue. Xanthorrhizole used in this research was isolate fromethyl acetate fraction of Curcuma xanthorrhizaRoxb. 'srhizome compared the result with pure xanthorrhizol . Thecytotoxic activity assay toward YMB-1 cell showed thatxantorrhizole has highest activity with ICso 2.88 glmL,followed by the volatile oil with IC,o 3.20 glmL.lt meansthatactivity of volatile oil was not significantly different comparedwith that of xanthorrhizole . The lowest activity was found onisolate C27 with ICso 4.80 g/ml, while antimycin as positivecontrol gave IC,o 1.03 glmL..Keywords: Curcumaxanthorrhiza Roxb., volatile oil,xanthorrhizol,breast cancer,YMB-1cell, alamar blue method